Economic well-being and non-economic well-being: A poverty of the meaning and measurement of poverty - Andrew Sumner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper discusses the measurement of poverty and well-being. A historical overview is given of the last fifty years. This is followed by discussion of three groupings of indicators: those measures based primarily on economic well-being; those based on non-economic well-being and composite indicators. It is argued that the choice of indicator should reflect its purpose and that economic measures are best when quick, rough-and-ready, short run, aggregate inferences are required. In contrast, non-economic measures are better when greater depth on medium- or longer-term trends and/or dis-aggregation are required. – data ; statistics ; poverty ; well-being
Keywords: I30; I31; I32; 330; Lebensqualität; Armut; Sozialer Indikator